Peripheral enthesitis assessed by whole-body MRI in axial spondyloarthritis: Distribution and diagnostic value - Guo, Zikang; Li, Boya; Zhang, Yimeng; Kong, Chunyu; Liu, Yang; Qu, Jin; Zhan, Ying; Shen, Zhiwei; Lei, Xinwei (Frontiers in Immunology, 2022)
Objective To determine the distribution and diagnostic value of peripheral enthesitis detected by whole-body MRI (WBMRI) in axial spondyloarthritis (axSpA) diagnosis, and to determine the value of the peripheral enthesitis score in axSpA assessment. Methods Sixty axSpA patients [mean age of 33.2 (24.8–40.6) years] and 50 controls with chronic low back pain (LBP) [mean age of 34.7 (28.3–41.1) years] were enrolled. The gold standard was physician’s comprehensive diagnosis based on current classification criteria and physical examination. All subjects underwent WBMRI, and 47 peripheral entheses were assessed for each patient with scores of 0–188. Results WBMRI identified 155 enthesitis sites in 78.3% (n = 47) patients with axSpA. Meanwhile, 23 enthesitis sites were identified in 32% (n = 16) controls. The pelvis had the maximum number of enthesitis sites (52, 33.5%) in axSpA patients. Pelvic and anterior chest wall enthesitis had the highest sensitivity (51.67%) and specificity (100%) in axSpA diagnosis, respectively. There were different manifestations of enthesitis subtypes between axSpA patients and the control group. Osteitis was more present than soft-tissue inflammation in axSpA patients. The AUC for the number of enthesitis sites was 0.819 (95% CI 0.739–0.899), and that for the enthesitis score was 0.833 (95% CI 0.755–0.910), indicating statistically significant differences (P = 0.025). Based on the Youden index and clinical need, three enthesitis sites (sensitivity of 53.33, specificity of 98, and Youden index of 0.51) and enthesitis score (sensitivity of 58.33, specificity of 98, and Youden index of 0.56) may have the greatest value for axSpA diagnosis. Conclusion The distribution of peripheral enthesitis can be adequately assessed by whole-body MRI, which could help diagnose axial spondyloarthritis. The enthesitis score may provide a more accurate assessment and diagnostic tool in axSpA compared with enthesitis site counting.